Yamuna Kachru and world Englishes. Issue 1 (March 2015) - BOLTON, KINGSLEY; SMITH, LARRY E.; SRIDHAR, S.N.
ABSTRACT Professor Yamuna Kachru brought an enormous energy and commitment to the world Englishes (WE) enterprise over three decades. Her research and publications were characterized by a unique intelligence, informed by her expert knowledge of South Asian linguistics, as well as a lively and curious intellect fascinated by many other aspects of language studies. Her contribution to world Englishes was lucidly informed by her own experiences of India and by her deep and comprehensive research on South Asian languages. The arc of her research career can be traced from South Asian linguistics through contrastive discourse analysis to a wide variety of research and publications on world Englishes, about which she co‐authored three volumes, and published more than forty research papers. Her work continues to serve as an inspiration for WE scholars and students throughout the world.